Vocational Identity Resources in Emerging Adulthood: Associations With Facets of Dispositional Mindfulness. Issue 1 (4th March 2021) - Feldt, Ronald; Bejar, Matthew; Lee, Jen; Louison, Rebecca
Abstract : The processes of career development and forming a crystallized identity can be fraught with emotional turmoil. One multidimensional construct known to reduce emotional reactivity is dispositional mindfulness (DM). We used canonical correlation analysis to examine relationships involving measures of resources for establishing a vocational identity (Hirschi, 2012a) and facets of DM in emerging adults (134 women, 38 men). Observing, describing, and nonreactivity to inner experiences contributed uniquely to the first canonical function with career agency and occupational engagement. Observing, describing, and nonjudging contributed uniquely to the second function with occupational engagement and negative career outlook. These results shed light on key facets of DM that help emerging adults to effectively utilize emotion within the context of career‐life planning. Future research should examine relationships between DM facets and additional constructs subsumed within the career resources model. Counselors may find utility in understanding how clients conceptualize conscious emotional experience and use it in career‐life planning.